Pengaruh Diklat dan Motivasi Kerja Terhadap Prestasi Kerja Pegawai Pusat Pengembangan Sumber Daya Manusia (PPSDM) Badan Narkotika Nasional Periode 2022-2023 - Rika Susilawati; Immas Nurhayati; Mohammad Jibriel Avessina (CV. ITTC INDONESIA, 2024)
The purpose of this study was to determine the effect of training and work motivation on work performance. The population in this study was 98 employees. Sampling using purposive sample techniques, the samples taken in this study were civil servants totaling 39 employees. This study used quantitative methods with data collection techniques using questionnaires containing a number of questions with Likert scale measurements. Based on the results of the study, there is a significant positive influence between training variables on work performance. There is a significant positive influence between work motivation variables on work performance, and there is a simultaneous influence between training variables and work motivation on work performance.